Associated congenital heart disease with Hirschsprung's disease: a retrospective cohort study on 2,174 children - Wu, Yujian; Zhu, Yun; Zhang, Xu; Feng, Jinqing; Xia, Huimin; Zhang, Yan; Li, Jia (Frontiers in Cardiovascular Medicine, 2023)
Objective To examine the incidence and phenotypes of congenital heart disease (CHD) in a large cohort of patients with Hirschsprung's disease (HSCR). Study design Retrospective data review of children with HSCR between 2003 and 2020 was conducted at the Provincial Key Laboratory for Structural Birth Defects in Guangzhou, Guangdong, China. HSCR was confirmed by pathological diagnosis. CHD was defined as a gross structural abnormality of the heart or intrathoracic great vessels that is of functional significance. Results A total of 2,174 HSCR patients (84.7% males) were studied and 306 of them underwent echocardiography. Overall, 27 children (1.2%) had associated CHD. Among them, CHDs mostly presented as atrial and ventricular septal defects (n = 5 and 12 respectively) and patent ductus arteriosus (n = 4). Three patients (1.4‰) presented as a severe CHD including complete atrioventricular canal, congenitally corrected transposition of the great arteries and double-outlet of right ventricle. Among 14 patients carrying a chromosomal abnormality, CHD was detected in 4 infants (28.6%), all being mild forms of septal defects. Conclusions Some new and severe types of CHD were found in patients with HSCR. Patients with syndromic features had higher incidence of CHD.